2011
DOI: 10.1016/j.ijpsycho.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The observer observed: Frontal EEG asymmetry and autonomic responses differentiate between another person's direct and averted gaze when the face is seen live

Abstract: Recently, we showed that another person's gaze direction influenced the perceiver's frontal EEG asymmetry and autonomic arousal in response to freely viewed real faces, but not in response to face pictures. However, the lack of a task during the viewing may have resulted in less attention allocation to face pictures vs. live faces. In the present study, the participants performed two online tasks while viewing the faces presented live through an electronic shutter and as pictures on a computer screen. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 50 publications
11
107
2
2
Order By: Relevance
“…As far as we know, the only previous study showing that females might not respond to direct gaze as strongly as males while performing a memory task was the study by Otteson and Otteson (1980) with primary school children. In previous studies investigating the effect of direct gaze on arousal, both females and males have been found to respond to direct gaze with enhanced arousal responses (Nichols & Champness, 1971;Helminen et al, 2011;Hietanen et al, 2008;Myllyneva & Hietanen, 2015;Pönkänen et al, 2011). Thus, we are cautious in drawing any conclusions about this result.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As far as we know, the only previous study showing that females might not respond to direct gaze as strongly as males while performing a memory task was the study by Otteson and Otteson (1980) with primary school children. In previous studies investigating the effect of direct gaze on arousal, both females and males have been found to respond to direct gaze with enhanced arousal responses (Nichols & Champness, 1971;Helminen et al, 2011;Hietanen et al, 2008;Myllyneva & Hietanen, 2015;Pönkänen et al, 2011). Thus, we are cautious in drawing any conclusions about this result.…”
Section: Discussionmentioning
confidence: 87%
“…However, our recent studies (Hietanen, Leppänen, Peltola, Linna-aho, & Ruuhiala, 2008;Myllyneva & Hietanen, 2015;Pönkänen, Peltola, & Hietanen, 2011) have indicated that the effect of eye contact on arousal is not solely a result of bottom-up visual processing of self-directed eyes, but arousal responses are strongly modulated by top-down cognitive processes. According to the studies by Hietanen et al (2008) and Pönkänen et al (2011), the arousing effect of direct gaze was evident in a situation where the other person was met face-to-face, but not when seeing a picture of the person's face on a computer monitor. The authors suggested that this might be related to awareness of being seen by another person.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have reported that sympathetic skin conductance responses (SCRs)—a robust indicator of affective arousal (Critchley, 2002)—are greater in conditions with another individual’s direct gaze rather than averted gaze or closed eyes (e.g., Nichols and Champness, 1971; Hietanen et al, 2008; Helminen et al, 2011; Pönkänen et al, 2011b; Myllyneva and Hietanen, 2015). Pupil dilation, another index of physiological arousal, has also been shown to be larger in response to direct- versus averted-gaze stimuli (Porter et al, 2006).…”
Section: Autonomic Arousal and Amygdala Activationmentioning
confidence: 99%
“…These signals have been shown to have distinct effects on the person receiving them. Experiencing direct gaze from a social partner, signaling interest and approach tendencies, can elicit approach-related left-sided asymmetry in anterior cortical activity while averted gaze, indicating lack of interest or avoidance, has been related to weaker left-sided or stronger right-sided asymmetry in cortical activity (Hietanen et al, 2008;Pönkänen et al, 2011). There is also evidence that Neuroticism or similar constructs are related to differences in gaze behavior and affective evaluations of gaze direction.…”
Section: Social Contact As a Trait-relevant Situation For Associatingmentioning
confidence: 99%
“…Taken together, these findings suggest that looking at another person with direct gaze should reveal Neuroticism-related differences in anterior EEG asymmetry. Note that observing such effects may require participants to look at another person presented "live" rather than pictures of faces presented on a computer screen (Hietanen et al, 2008;Pönkänen et al, 2011). The live condition adds authenticity as participants are aware of being looked at and perceive the potential for interaction with the stimulus person.…”
Section: Social Contact As a Trait-relevant Situation For Associatingmentioning
confidence: 99%